Positive electrode slurry composition and lithium secondary battery manufactured using the same

CN116918094BActive Publication Date: 2026-11-03LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280015253.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-20
Filing Date
2022-12-21
Publication Date
2026-11-03
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

The lithium iron phosphate cathode slurry has a particle agglomeration problem, which leads to high viscosity, poor stability and coating processability, and increased discharge resistance.

Method used

A dispersant with a weight-average molecular weight of 10,000 g/mol to 150,000 g/mol is used in combination with lithium iron phosphate and conductive materials to form spherical agglomerates, thereby inhibiting particle aggregation and improving dispersibility and conductive network.

Benefits of technology

It reduces the discharge resistance of lithium secondary batteries, improves the stability and coating processability of positive electrode slurry, shortens manufacturing time, and reduces process costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116918094B_ABST
    Figure CN116918094B_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode slurry composition comprising a positive electrode active material, a dispersant, a conductive material, a binder, and a solvent, wherein the positive electrode active material comprises lithium iron phosphate, and the dispersant has a weight average molecular weight of 10,000 g / mol to 150,000 g / mol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to Korean Patent Application No. 10-2021-0187722, filed on December 24, 2021, and Korean Patent Application No. 10-2022-0179775, filed on December 20, 2022, the disclosures of which are incorporated herein by reference.

[0002] This invention relates to a positive electrode slurry composition and a lithium secondary battery manufactured using the same, and more specifically, to a positive electrode slurry composition comprising a low molecular weight dispersant and a lithium secondary battery manufactured using the same. Background Technology

[0003] With the technological advancements and increasing demands for electric vehicles and energy storage systems (ESS), the need for batteries as energy sources is rapidly growing. Consequently, various studies have been conducted on batteries capable of meeting diverse requirements. In particular, lithium-ion secondary batteries, exhibiting excellent lifespan and cycle characteristics while possessing high energy density, are being actively researched as power sources for devices.

[0004] Lithium cobalt oxides, lithium nickel cobalt manganese oxides, and lithium iron phosphates have been used as positive electrode active materials for lithium secondary batteries.

[0005] Of the types listed above, lithium iron phosphate (LFP) is inexpensive due to its abundant resources and inclusion of low-cost iron. Furthermore, LFP's low toxicity reduces environmental pollution when used. Additionally, LFP's olivine structure allows for stable maintenance of the active material structure at high temperatures, compared to the layered structure of lithium transition metal oxides. Therefore, the battery exhibits excellent high-temperature stability and long-term lifespan characteristics.

[0006] However, compared to lithium transition metal oxides such as lithium nickel cobalt manganese oxides, lithium iron phosphates suffer from poor lithium mobility and low conductivity. Therefore, lithium iron phosphates with small average particle size are typically used to shorten the lithium migration path, the surface of lithium iron phosphates is coated with carbon to improve conductivity, and excess conductive material is used.

[0007] However, as the particle size of lithium iron phosphate (LFP) decreases, its specific surface area increases, and carbon-coated LFP exhibits reduced wettability relative to the solvent. Consequently, severe particle agglomeration of LFP occurs, reducing the stability and coating processability of the cathode slurry. Furthermore, when an excessive amount of conductive material is used, excessive agglomeration between conductive material particles occurs in the cathode slurry. As the amount of agglomerated conductive material increases, the amount of LFP capable of participating in the battery charge / discharge reaction relatively decreases, potentially increasing the charge / discharge resistance of the lithium secondary battery.

[0008] Therefore, there is a need for technology to suppress particle agglomeration in cathode slurry compositions containing lithium iron phosphate and in cathodes. Summary of the Invention

[0009] Technical issues

[0010] The present invention aims to provide a positive electrode slurry composition with relatively low viscosity and relatively high solids content by improving the dispersibility of positive electrode active materials and / or conductive materials in the positive electrode slurry composition and inhibiting particle agglomeration.

[0011] The present invention also aims to provide a lithium secondary battery with reduced discharge resistance by improving the dispersion of the positive electrode active material and / or conductive material in the positive electrode and suppressing particle aggregation.

[0012] Technical solution

[0013] According to one embodiment of the present invention, a positive electrode slurry composition is provided, the positive electrode slurry composition comprising a positive electrode active material, a dispersant, a conductive material, a binder, and a solvent, wherein the positive electrode active material comprises lithium iron phosphate, and the dispersant has a weight-average molecular weight of 10,000 g / mol to 150,000 g / mol.

[0014] According to another embodiment of the present invention, a lithium secondary battery is provided, the lithium secondary battery comprising a positive electrode, wherein the positive electrode comprises a positive electrode active material, a dispersant, a conductive material and a binder, the positive electrode active material comprising lithium iron phosphate, and the dispersant having a weight-average molecular weight of 10,000 g / mol to 150,000 g / mol.

[0015] Beneficial effects

[0016] Because the cathode slurry composition according to the present invention contains a dispersant having a low weight-average molecular weight, the solvent wettability and dispersibility of the lithium iron phosphate particles contained in the cathode slurry composition are improved, thereby suppressing the agglomeration of lithium iron phosphate particles. Therefore, compared with other cathode slurry compositions having the same viscosity, this cathode slurry composition can have a low viscosity and also a high solids content.

[0017] Furthermore, since it can suppress the particle aggregation of lithium iron phosphate, it can improve the stability and coating processability of the cathode slurry composition.

[0018] Furthermore, since the cathode slurry composition according to the present invention has a relatively high solids content, the time required for the slurry drying process in the manufacture of the cathode is shortened, thereby reducing process costs.

[0019] Furthermore, due to the low weight-average molecular weight of the dispersant, the conductive material aggregates in a spherical morphology within the positive electrode, thereby minimizing the surface area of ​​the aggregated conductive material compared to that aggregated in a linear morphology. Consequently, the surface area of ​​the positive electrode active material positioned adjacent to the aggregated conductive material and thus not participating in the lithium intercalation / deintercalation reaction is minimized, thereby reducing the discharge resistance of lithium secondary batteries manufactured using the positive electrode slurry composition. Attached Figure Description

[0020] Figure 1 This is a scanning electron microscope (SEM) image of the cross-section of the positive electrode in the lithium secondary battery of Example 1.

[0021] Figure 2 This is a SEM image of the cross-section of the positive electrode in the lithium secondary battery of Example 2.

[0022] Figure 3 This is a SEM image of the cross-section of the positive electrode in the lithium secondary battery of Example 3.

[0023] Figure 4 This is a SEM image of the cross-section of the positive electrode in the lithium secondary battery of Comparative Example 1. Detailed Implementation

[0024] The advantages and features of the invention, as well as the methods for implementing the invention, will become apparent from the exemplary embodiments described below with reference to the accompanying drawings. However, the invention is not limited to the exemplary embodiments described below and can be implemented in various different forms. Rather, the exemplary embodiments provided make the disclosure of the invention sufficient and complete, and fully inform those skilled in the art of the scope of the invention, which is defined only by the scope of the claims. Throughout the specification, the same reference numerals denote the same elements.

[0025] Unless otherwise defined, all terms used herein, including technical or scientific terms, shall be interpreted as having the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Therefore, unless explicitly defined, terms such as those defined in common dictionaries should not be interpreted in an ideal or overly formal sense.

[0026] The terminology used herein is for describing exemplary embodiments and is not intended to limit the invention. In this specification, the singular form may include the plural form unless specifically stated in the phrase. As used herein, the terms “comprising” and / or “including” do not exclude the presence or addition of more than one other component in addition to those mentioned.

[0027] In this specification, when a component is referred to as "containing," "comprising," "including," or "having" another component, it should be understood that, unless otherwise expressly stated, the component does not exclude other components but may also contain other components.

[0028] In this specification, references to "A and / or B" mean A, B, or A and B.

[0029] In this specification, unless otherwise expressly stated, “%” refers to weight%.

[0030] In this specification, D 50 This refers to the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. (D) 50 It can be measured, for example, by laser diffraction. Laser diffraction can typically measure particle sizes in the submicron to millimeter range and can obtain results with high reproducibility and high resolution.

[0031] In this manual, the "specific surface area" is measured by the BET method, and can be specifically calculated from the amount of adsorbed nitrogen using the BELSORP-mini II, which is available from BEL Japan, at liquid nitrogen temperature (77K).

[0032] In this specification, after cooling the positive electrode slurry composition at room temperature and 1% relative humidity for one hour, the viscosity was measured using a viscometer (Brookfield) at 25°C and 10... -2 The viscosity of the cathode slurry composition was measured at a shear rate of rpm. This viscosity measurement was performed over a period of 2 hours, including the cooling time following the preparation of the cathode slurry composition.

[0033] In this specification, the SOC50 discharge resistor refers to the value obtained by dividing the voltage drop observed when a discharge pulse is applied for 10 seconds at 50% state of charge (SOC) and 2.5C by the current value.

[0034] The embodiments of the present invention will be described in detail below.

[0035] Positive electrode slurry composition

[0036] The positive electrode slurry composition according to an embodiment of the present invention is intended to form a positive electrode active material layer and comprises a positive electrode active material, a dispersant, a conductive material, a binder, and a solvent, wherein the positive electrode active material comprises lithium iron phosphate, and the dispersant has a weight-average molecular weight of 10,000 g / mol to 150,000 g / mol.

[0037] In conventional cathode slurry compositions containing lithium iron phosphate (LFP), excessive particle agglomeration of LFP occurs due to the small particle size of LFP and the carbon coating formed on its surface, thereby reducing the stability and coating processability of the cathode slurry. Furthermore, when an excessive amount of conductive material is used to improve the conductivity of the cathode, excessive agglomeration of the conductive material particles occurs, thus degrading the conductive network of the cathode. As a result, the charging / discharging resistance of the lithium secondary battery increases.

[0038] As a result of long-term research to solve the above-mentioned problems, the inventors of this invention have discovered that when a low weight-average molecular weight dispersant is included in the positive electrode slurry composition, the dispersibility of the positive electrode active material and / or conductive material in the positive electrode slurry composition can be improved, and particle agglomeration can be suppressed. This will be described in detail below.

[0039] (1) Positive electrode active material

[0040] The positive electrode active material can contain lithium iron phosphate. When the positive electrode active material contains lithium iron phosphate, the stability of the positive electrode containing the positive electrode active material is significantly improved, thus the ignition of lithium secondary batteries containing the positive electrode can be significantly reduced.

[0041] Lithium iron phosphate can be a compound represented by the following chemical formula 1.

[0042] [Chemical Formula 1]

[0043] Li 1+a Fe 1-x M x (PO 4-b )X b

[0044] (In chemical formula 1,

[0045] M contains one or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y.

[0046] X contains one or more elements selected from F, S, and N, and a, b, and x satisfy -0.5 ≤ a ≤ 0.5, 0 ≤ b ≤ 0.1, and 0 ≤ x ≤ 0.5, respectively.

[0047] For example, lithium iron phosphate can be LiFePO4.

[0048] Lithium iron phosphate can be contained in a carbon coating on its surface. When the carbon coating forms on the surface of lithium iron phosphate, the conductivity is enhanced, thereby improving the resistive characteristics of the positive electrode.

[0049] The carbon coating can be formed using at least one raw material selected from the following: glucose, sucrose, lactose, starch, oligosaccharides, polyoligosaccharides, fructose, cellulose, furfuryl alcohol polymers, block copolymers of ethylene and ethylene oxide, ethylene resins, cellulose resins, phenolic resins, asphalt resins, and tar resins. Specifically, the carbon coating can be formed by mixing the raw material with lithium iron phosphate and heat-treating the resulting mixture.

[0050] The average particle size D of lithium iron phosphate 50 The particle size can range from 0.8 μm to 20.0 μm, specifically from 0.9 μm to 10.0 μm, and more specifically from 0.9 μm to 3.0 μm. When the average particle size D of the positive electrode active material... 50 When the above range is met, the lithium mobility in lithium iron phosphate is improved, thereby improving the charge / discharge characteristics of the battery.

[0051] The BET specific surface area of ​​lithium iron phosphate can be 5 m². 2 / g to 20m 2 / g, specifically 7m 2 / g to 18m 2 / g, more specifically 9m 2 / g to 16m 2 / g. Compared to conventional lithium iron phosphate, the above range represents a low BET specific surface area range. When the above range is met, the agglomeration of lithium iron phosphate can be effectively suppressed even in cathode slurry compositions with relatively small amounts of dispersant.

[0052] Based on the total solids content of the cathode slurry composition, the lithium iron phosphate content can be from 93% to 98% by weight, specifically from 93.5% to 98% by weight, and more specifically from 94% to 97% by weight. When the lithium iron phosphate content meets the above range, sufficient energy density of the cathode is ensured, thereby improving the battery capacity of the cathode.

[0053] (2) Dispersant

[0054] The dispersant inhibits the excessive aggregation of lithium iron phosphate in the positive electrode slurry composition and effectively disperses lithium iron phosphate in the prepared positive electrode active material layer.

[0055] The dispersant may contain hydrogenated nitrile copolymers. Specifically, the dispersant may be a hydrogenated nitrile copolymer.

[0056] Specifically, the hydrogenated nitrile copolymer can be a copolymer comprising structural units derived from α,β-unsaturated nitriles and structural units derived from hydrogenated conjugated dienes, or a copolymer comprising structural units derived from α,β-unsaturated nitriles, structural units derived from conjugated dienes, and structural units derived from hydrogenated conjugated dienes. As α,β-unsaturated nitrile monomers, acrylonitrile, methacrylonitrile, etc., can be used, either alone or in combination of two or more thereof. As conjugated diene monomers, C4 to C6 conjugated diene monomers, such as 1,3-butadiene, isoprene, 2,3-methylbutadiene, etc., can be used, either alone or in combination of two or more thereof.

[0057] More specifically, the hydrogenated nitrile copolymer can be hydrogenated nitrile butadiene rubber (H-NBR).

[0058] The weight-average molecular weight of the dispersant can be from 10,000 g / mol to 150,000 g / mol, preferably from 15,000 g / mol to 140,000 g / mol, and more preferably from 20,000 g / mol to 130,000 g / mol. This value is lower than the weight-average molecular weight of dispersants contained in conventional cathode slurry compositions.

[0059] When the weight-average molecular weight of the dispersant is less than 10,000 g / mol, the dispersibility of lithium iron phosphate decreases, and the dispersant may dissolve during electrode preparation. When the weight-average molecular weight of the dispersant exceeds 150,000 g / mol, the positive electrode slurry composition has high viscosity, which may reduce the stability and coating processability of the positive electrode slurry composition, and the conductive material may agglomerate in a linear morphology. Therefore, this is not preferable in terms of the resistance of the lithium secondary battery.

[0060] On the other hand, when the weight-average molecular weight of the dispersant meets the above-mentioned range, the solvent wettability and dispersibility of lithium iron phosphate particles are improved, thereby inhibiting the agglomeration of lithium iron phosphate particles. Therefore, compared with other cathode slurry compositions with the same viscosity, this cathode slurry composition can have low viscosity and high solids content.

[0061] Furthermore, when the weight-average molecular weight of the dispersant meets the aforementioned range, the conductive material aggregates in a spherical morphology within the positive electrode. This minimizes the surface area of ​​the aggregated conductive material compared to conductive material aggregated in a linear morphology. Consequently, the surface area of ​​the positive electrode active material positioned adjacent to the aggregated conductive material and thus not participating in the lithium intercalation / deintercalation reaction is minimized, thereby reducing the discharge resistance of lithium secondary batteries manufactured using the positive electrode slurry composition.

[0062] Based on the total solids content of the cathode slurry composition, the content of the dispersant can be from 0.2 wt% to 1.0 wt%, specifically from 0.2 wt% to 0.9 wt%, and more specifically from 0.3 wt% to 0.8 wt%. When the content of the dispersant meets the above range, the agglomeration of conductive materials in the cathode active material layer is suppressed, thereby improving the conductive network of the cathode.

[0063] (3) Adhesive

[0064] Adhesives are used to help bond positive electrode active materials, conductive materials, etc., to each other and to current collectors. Specific examples include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber, and various copolymers thereof, which can be used alone or in combination of two or more.

[0065] Based on the total solids content of the cathode slurry composition, the binder content can be from 2.0 wt% to 4.0 wt%, specifically from 2.2 wt% to 3.8 wt%, and more specifically from 2.3 wt% to 3.7 wt%. When the binder content meets the above range, the contact area between the binder and lithium iron phosphate increases, thereby ensuring excellent cathode adhesion.

[0066] (4) Conductive materials

[0067] There are no particular limitations on the conductive material, as long as it does not cause a chemical change in the battery and is conductive. Examples of materials that can be used include graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermally cracked carbon black; conductive fibers such as carbon fibers and metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives. Specific examples of commercially available conductive materials include acetylene black products (Chevron Chemical Company), Denka Black (Denka Singapore Private Limited), Gulf Oil Company products, Ketjen black, EC products (Armak Company), Vulcan XC-72 (Cabot Company), and Super P (Timcal). Preferably, the conductive material can be carbon nanotubes. Since the conductive network of carbon nanotubes can mitigate the migration of binders during the drying process of the cathode slurry composition, carbon nanotubes are particularly preferred as the conductive material contained in the cathode slurry composition of the present invention.

[0068] Based on the total solids content of the positive electrode slurry composition, the content of conductive material can be from 0.1 wt% to 3.0 wt%, specifically from 0.2 wt% to 2.0 wt%, and more specifically from 0.6 wt% to 1.2 wt%. When the content of conductive material meets the above range, the conductive network of the positive electrode is ensured, thereby improving the conductivity of the positive electrode.

[0069] (5) Solvent

[0070] The solvent is intended to mix the aforementioned positive electrode active material, binder, dispersant, and / or conductive material. Any solvent commonly used in the art can be used as a solvent, examples of which include dimethyl sulfoxide (DMSO), isopropanol, N-methyl-2-pyrrolidone (NMP), acetone, water, etc., which can be used alone or in combination of two or more thereof.

[0071] The solvent content allows the cathode slurry composition to have appropriate viscosity and solids content. For example, the solvent content can result in a solids content of 40% to 75% by weight, specifically 50% to 70% by weight, and more specifically 55% to 70% by weight. This content is relatively higher than that of other conventional cathode slurry compositions. When the solids content of the cathode slurry composition meets the above range, the time required for the slurry drying process in cathode manufacturing is shortened, thereby reducing process costs. Furthermore, the composition has a coatable viscosity, and the cathode active material layer formed by the composition has a thickness exceeding a certain level, thereby ensuring excellent energy density.

[0072] The positive electrode slurry composition according to an embodiment of the present invention is subjected to 25°C and 10 -2 Viscosities measured at shear rates of rpm can range from 5,000 cps to 20,000 cps, specifically from 6,000 cps to 15,000 cps, and more specifically from 8,000 cps to 15,000 cps. Positive electrode slurry compositions with viscosities within this range exhibit excellent storage stability and coating processability. Furthermore, compared to other positive electrode slurry compositions with the same viscosity, these compositions can have a higher solids content, thereby reducing the time required for the slurry drying process in positive electrode manufacturing and thus lowering process costs.

[0073] positive electrode

[0074] Next, the positive electrode according to the present invention will be described.

[0075] The positive electrode comprises a positive current collector and a positive active material layer located on at least one surface of the positive current collector. In this case, the positive active material layer comprises a positive active material, a conductive material, a binder, and a dispersant, wherein the positive active material comprises lithium iron phosphate, and the dispersant has a weight-average molecular weight of 10,000 g / mol to 150,000 g / mol. The positive electrode can be formed using the above-described positive electrode slurry composition. The positive active material, binder, dispersant, and conductive material have been described above.

[0076] Since the cathode according to the present invention contains hydrogenated nitrile butadiene rubber as a dispersant, and the weight-average molecular weight of the dispersant is 10,000 g / mol to 150,000 g / mol, the conductive material aggregates in a spherical form in the cathode. In the case of the cathode, the surface area of ​​the aggregated conductive material can be minimized compared to conductive material aggregated in a linear form. Therefore, the surface area of ​​the cathode active material positioned adjacent to the aggregated conductive material and thereby not participating in the lithium intercalation / deintercalation reaction is minimized, thereby reducing the discharge resistance of the lithium secondary battery.

[0077] In the case of the positive electrode according to the present invention, the conductive material agglomerates in a spherical shape, and therefore, the maximum major axis length of the agglomerated region of the conductive material in the cross-section of the positive electrode is 10 μm or less. Furthermore, the ratio of the minor axis length to the major axis length of the agglomerated region of the conductive material can be 0.1:1, preferably 0.2:1, and more preferably 0.3:1.

[0078] When the agglomeration region of the conductive material meets the above-mentioned range, the discharge resistance of the lithium secondary battery can be enhanced.

[0079] Agglomeration regions of conductive material in the cross-section of the cathode can be identified by observing the cross-section using a scanning electron microscope (SEM). In SEM images or backscattered electron (BSE) images obtained by photographing the cross-section of the cathode, lithium iron phosphate appears as a bright contrast, while the agglomeration regions of conductive material appear as a dark contrast. The lengths of the major and minor axes of the agglomeration regions of conductive material exhibiting dark contrast can be measured.

[0080] In this invention, a 50 μm × 50 μm area in the cross-section of the positive electrode is observed using SEM, and the lengths of the major and minor axes of the area, shown as shadows in the SEM or BSE image, are measured.

[0081] There are no particular restrictions on the positive electrode current collector, as long as it does not cause a chemical change in the battery and is conductive. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc., can be used as the current collector.

[0082] The thickness of the positive electrode current collector can range from 3 μm to 500 μm, and it can have fine irregularities formed on its surface to increase adhesion to the positive electrode active material layer. For example, the positive electrode current collector can be used in any of the various forms such as film, sheet, foil, mesh, porous body, foam, nonwoven fabric, etc.

[0083] The positive electrode active material layer may be located on at least one surface of the positive electrode current collector and is formed by the above-described positive electrode slurry composition.

[0084] In addition to using the above-mentioned positive electrode slurry composition, the positive electrode can be manufactured using conventional methods for manufacturing positive electrodes. Specifically, the positive electrode can be manufactured by coating the positive electrode slurry composition onto a positive electrode current collector, followed by drying and pressing.

[0085] As an alternative method, the positive electrode can be manufactured by laminating a membrane onto the positive electrode current collector, wherein the membrane is obtained by casting a positive electrode slurry composition onto a separate carrier and removing it from the carrier.

[0086] Lithium secondary batteries

[0087] Next, the lithium secondary battery according to the present invention will be described.

[0088] The lithium secondary battery includes a positive electrode, a negative electrode, a separator between the positive and negative electrodes, and an electrolyte.

[0089] The positive electrode in a lithium secondary battery has been described above. For example, the positive electrode comprises a positive electrode active material, a conductive material, a binder, and a dispersant, wherein the positive electrode active material comprises lithium iron phosphate, and the weight-average molecular weight of the dispersant is from 10,000 g / mol to 150,000 g / mol.

[0090] The negative electrode can be manufactured, for example, by preparing a negative electrode forming composition comprising a negative electrode active material, a negative electrode binder and a negative electrode conductive material, and then coating the composition onto a negative electrode current collector.

[0091] There are no particular restrictions on the negative electrode active material, and any compound capable of reversibly inserting and deintercalating lithium can be used. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fibers, amorphous carbon, and highly crystalline carbon; (semi-metallic) materials capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; and composite materials containing both (semi-metallic) materials and carbonaceous materials. Examples of low-crystallinity carbon include soft carbon and hard carbon, while examples of highly crystalline carbon include natural graphite, condensed graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature calcined carbon, such as coke derived from petroleum or coal tar pitch, which can be used alone or in combination of two or more of them. Furthermore, lithium metal thin films can be used as negative electrode active materials.

[0092] The negative electrode conductive material is used to impart conductivity to the electrode, and there are no particular limitations on the use of any conductive material that does not cause chemical changes in the battery and is conductive. Specific examples include graphite, such as natural graphite, artificial graphite, etc.; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking black, carbon fiber, carbon nanotubes, etc.; metal powders or fibers such as copper, nickel, aluminum, silver, etc.; conductive whiskers, such as zinc oxide, potassium titanate, etc.; conductive metal oxides, such as titanium oxide, etc.; and conductive polymers, such as polyphenylene derivatives, etc., which can be used alone or in combination of two or more thereof. The content of the negative electrode conductive material relative to the total weight of the negative electrode active material layer is typically 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight.

[0093] The negative electrode binder is used to enhance the adhesion between negative electrode active material particles and the adhesion between the negative electrode active material and the negative electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), PVDF-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, which can be used alone or in combination of two or more thereof. The content of the negative electrode binder relative to the total weight of the negative electrode active material layer can be 1 to 30% by weight, preferably 1 to 20% by weight, more preferably 1 to 10% by weight.

[0094] On the other hand, there are no particular restrictions on the negative electrode current collector, as long as it does not cause chemical changes in the battery and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, or copper or stainless steel, aluminum-cadmium alloys whose surfaces are treated with carbon, nickel, titanium, silver, etc., can be used as negative electrode current collectors.

[0095] Furthermore, the thickness of the negative electrode current collector can typically range from 3 μm to 500 μm. Similar to the positive electrode current collector, the negative electrode current collector can have fine irregularities formed on its surface to increase adhesion to the negative electrode active material. For example, the negative electrode current collector can be used in any of various forms such as membranes, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0096] On the other hand, as the separator in a lithium-ion secondary battery, any separator commonly used in lithium-ion secondary batteries can be used without particular limitation. In particular, separators exhibiting low resistance to electrolyte ion migration and excellent electrolyte impregnation ability are preferred. Specifically, porous polymer membranes can be used, such as porous polymer membranes made of polyolefin polymers such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, ethylene / methacrylate copolymer, etc., or having a stacked structure of two or more layers thereof. Alternatively, conventional porous nonwoven fabrics can be used, such as nonwoven fabrics made of high-melting-point glass fiber, polyethylene terephthalate fiber, etc. Furthermore, the separator can be a porous film with a pore size of 0.01 μm to 10 μm and a thickness of 5 μm to 300 μm.

[0097] On the other hand, in lithium secondary batteries, the electrolyte can contain organic solvents and lithium salts commonly used in electrolytes, and there are no particular restrictions on them.

[0098] As an organic solvent, any solvent that can act as a medium through which ions participating in the electrochemical reaction of the battery can move is not particularly limited. Specifically, as organic solvents, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, ε-caprolactone, etc.; ether solvents such as dibutyl ether, tetrahydrofuran, etc.; ketone solvents such as cyclohexanone, etc.; aromatic hydrocarbon solvents such as benzene, fluorobenzene, etc.; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), etc.

[0099] Among those listed above, carbonate solvents are preferred, and more preferably mixtures of cyclic carbonate compounds (e.g., EC, PC, etc.) with high ionic conductivity and high dielectric constant and linear carbonate compounds (e.g., EMC, DMC, DEC, etc.) with low viscosity, said mixtures can improve the charge / discharge performance of the battery.

[0100] As lithium salts, any compound capable of providing lithium ions for use in lithium secondary batteries can be used without particular limitation. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc., can be used. The lithium salt is preferably contained in the electrolyte at a concentration of about 0.6 mol% to 2 mol%.

[0101] In addition to the electrolyte components mentioned above, to improve battery life characteristics, suppress battery capacity reduction, and increase battery discharge capacity, the electrolyte may further contain one or more additives, such as pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamine, nitrobenzene derivatives, sulfur, quinone imine dyes, and N-substituted compounds. Alzolidinediones, N,N-substituted imidazolidinediols, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol, aluminum trichloride, etc. In this case, the content of the additive can be 0.1% to 5% by weight relative to the total weight of the electrolyte.

[0102] The lithium secondary battery according to the present invention can be manufactured by the following steps: inserting a separator between a positive electrode and a negative electrode to form an electrode assembly, placing the electrode assembly in a cylindrical battery case or a prismatic battery case, and injecting an electrolyte. Alternatively, the lithium secondary battery can be manufactured by the following steps: stacking electrode assemblies, impregnating the electrode assemblies with an electrolyte, placing the result in a battery case, and sealing the battery case.

[0103] In the manufacture of the lithium secondary battery according to the present invention, the electrode assembly can be dried to remove one or more organic solvents selected from N-methyl-2-pyrrolidone (NMP), acetone, ethanol, PC, EMC, EC, and DMC used in the manufacture of the positive electrode. When an electrolyte having the same composition as the organic solvent used in the manufacture of the positive electrode is used, the drying step of the electrode assembly can be omitted.

[0104] Unlike the lithium secondary battery described above, the lithium secondary battery according to another embodiment of the present invention can be a solid-state battery.

[0105] As the battery casing, any battery casing commonly used in the art can be used, and there are no restrictions on the external shape depending on the intended use of the battery. For example, the external shape of the battery casing can be cylindrical, prismatic, pouch-shaped, coin-shaped, etc., similar to a can.

[0106] The lithium secondary battery according to the present invention can be used in the following fields due to its stable and excellent discharge capacity, output characteristics and capacity retention: portable devices, such as mobile phones, laptops, digital cameras, etc.; energy storage systems (ESS); and electric vehicles, such as hybrid electric vehicles (HEVs).

[0107] The battery resistance (SOC50 discharge resistance) of the lithium secondary battery according to the present invention can be less than 1.7mΩ, specifically from 1.1mΩ to 1.7mΩ, more specifically from 1.1mΩ to 1.6mΩ, said battery resistance being obtained by dividing the voltage drop value displayed when a discharge pulse is applied for 10 seconds at 50% state of charge (SOC) and 2.5C by the current value.

[0108] Since the positive electrode active material in a lithium-ion secondary battery contains lithium iron phosphate, and the weight-average molecular weight of the dispersant is between 10,000 g / mol and 150,000 g / mol, a battery resistance within the aforementioned range can be achieved. Specifically, when a low molecular weight dispersant is included in the positive electrode slurry composition, the conductive material aggregates in a spherical form in the positive electrode, thereby minimizing the surface area of ​​the aggregated conductive material compared to conductive material aggregated in a linear form. As a result, the surface area of ​​the positive electrode active material positioned adjacent to the aggregated conductive material and thus not participating in the lithium intercalation / deintercalation reaction is minimized, thereby reducing the battery resistance of the lithium-ion secondary battery manufactured using the positive electrode slurry composition to the aforementioned range.

[0109] The invention will be described in further detail below with reference to examples. However, the examples provided are merely illustrative of the invention, and the scope of the invention is not limited to these examples.

[0110] Example 1

[0111] (1) Preparation of positive electrode slurry composition

[0112] The average particle size D, which is used as the positive electrode active material 50 It has a thickness of 1 μm and a BET specific surface area of ​​11 m². 2LiFePO4, carbon nanotubes (CNTs) as conductive material, polyvinylidene fluoride (PVdF) as binder, and hydrogenated nitrile butadiene rubber (H-NBR) with a weight average molecular weight (Mw) of 40,000 g / mol as dispersant were added to N-methylpyrrolidone (NMP) solvent, and then mixed at 2500 rpm for 60 minutes using a homogeneous mixer (homogeneous disperser) to prepare a positive electrode slurry composition.

[0113] The positive electrode active material, conductive material, binder and dispersant in the positive electrode slurry composition exist in a weight ratio of 95.68:0.8:3.0:0.52, and the solid content in the positive electrode slurry composition is 60% by weight.

[0114] (2) Manufacturing of the positive electrode

[0115] The prepared positive electrode slurry composition was coated onto a 15 μm thick aluminum film using a die-casting machine, and then vacuum dried at 130 °C for 10 hours. Following this, pressing was performed to achieve a porosity of 28% for the positive electrode active material layer, thus fabricating the positive electrode. The positive electrode active material layer had a thickness of 98 μm, a width of 33 mm, a length of 50 mm, and a loading of 3.6 mAh / cm². 2 .

[0116] (3) Manufacturing of lithium secondary batteries

[0117] First, artificial graphite as the negative electrode active material, Super C as the conductive material, and SBR / CMC as the binder are mixed in a weight ratio of 96:1:3 to prepare a negative electrode slurry. The slurry is then coated onto one surface of a copper current collector, dried at 130°C, and pressed to make the porosity of the negative electrode active material layer 29%, in order to manufacture a negative electrode with a width of 34 mm and a length of 51 mm.

[0118] Next, an 18 μm thick polypropylene separator is inserted between the manufactured positive and negative electrodes to fabricate an electrode assembly. The electrode assembly is then housed in an aluminum pouch-type battery case, and 230 g of an electrolyte containing 1.0 M LiPF6 and 2 wt% vinylene carbonate (VC) dissolved in an organic solvent (EC / EMC / DMC = 3:3:4 volume ratio) is injected. The battery case is then vacuum-sealed. The electrolyte is aged for one day, activated at 7.9 mAh for 3 hours, and then further aged for 3 days. Finally, a degassing process is performed to manufacture the lithium-ion secondary battery.

[0119] Examples 2 to 3

[0120] The positive electrode slurry composition and lithium secondary battery were manufactured in the same manner as in Example 1, except that H-NBR having the weight-average molecular weight (Mw) described in Table 1 was used as a dispersant.

[0121] Comparative Example 1

[0122] The positive electrode slurry composition and lithium secondary battery were manufactured in the same manner as in Example 1, except that H-NBR with a weight-average molecular weight (Mw) of 220,000 g / mol was used as a dispersant and the solids content in the positive electrode slurry composition was 58% by weight.

[0123] Comparative Example 2

[0124] The positive electrode slurry composition and the lithium secondary battery were manufactured in the same manner as in Comparative Example 1, except that the solid content in the positive electrode slurry composition was 60% by weight.

[0125] Table 1

[0126]

[0127] Experimental Example 1 - Viscosity Measurement

[0128] The viscosity of each positive electrode slurry composition prepared in Examples 1 to 3 and Comparative Examples 1 and 2 was measured, and the measurement results are shown in Table 2 below.

[0129] Specifically, the various positive electrode slurry compositions prepared in Examples 1 to 3 and Comparative Examples 1 and 2 were cooled at room temperature and 1% relative humidity for one hour, and then tested using a viscometer (Brookfield) at 25°C and 10... -2 The viscosity of the cathode slurry composition was measured at a shear rate of rpm. This viscosity measurement was performed over a period of 2 hours, including the cooling time following the preparation of the cathode slurry composition.

[0130] Experimental Example 2 - Confirmation of the Agglomeration Morphology of Conductive Material on the Cross-Section of the Positive Electrode

[0131] Scanning electron microscopy (SEM) was used to observe a 50 μm × 50 μm area in the cross-section of each positive electrode manufactured in Examples 1 to 3 and Comparative Example 1, and to confirm the agglomeration morphology of the conductive material on the cross-section of the positive electrode. SEM images are shown below. Figure 1 and Figure 4 As shown in Table 2, the agglomeration morphology of the conductive material on the cross-section of the positive electrode is as follows.

[0132] Figure 1 This is a SEM image of the cross-section of the positive electrode in the lithium secondary battery of Example 1. Figure 2 This is a SEM image of the cross-section of the positive electrode in the lithium secondary battery of Example 2. Figure 3This is a SEM image of the cross-section of the positive electrode in the lithium secondary battery of Example 3. Figure 4 This is a SEM image of the cross-section of the positive electrode in the lithium secondary battery of Comparative Example 1.

[0133] exist Figures 1 to 4 In the image, lithium iron phosphate is shown as a bright area, while the agglomerated areas of conductive material are shown as a dark shading.

[0134] like Figures 1 to 2 As shown, in the cross-section of the positive electrode in Examples 1 and 2, it can be confirmed that no region of conductive material agglomerating in a linear form was found, and the conductive material agglomerating in a spherical form. Figure 3 As shown, in the cross-section of the positive electrode in Example 3, there are regions where the conductive material agglomerates in a spherical shape and regions where the conductive material agglomerates in a linear shape, but the maximum major axis length of the region where the conductive material agglomerates in a linear shape is less than 10 μm. On the other hand, as... Figure 4 As shown, in the cross-section of the positive electrode of Comparative Example 1, linear conductive material agglomerates with a length of more than 1 μm were found, as well as three conductive material agglomerates with a major axis length greater than 10 μm.

[0135] Experiment Example 3 - Measurement of Battery Resistance of Lithium Secondary Battery

[0136] The battery resistance of each lithium secondary battery prepared in Examples 1 to 3, as well as Comparative Examples 1 and 2, was measured, and the measurement results are shown in Table 2 below.

[0137] Specifically, for each lithium secondary battery manufactured in Examples 1 to 3 and Comparative Examples 1 and 2, the battery resistance (SOC50 discharge resistance) was measured by dividing the voltage drop value displayed when a discharge pulse was applied for 10 seconds at 50% state of charge (SOC) and 2.5C by the current value.

[0138] Table 2

[0139] Positive electrode slurry composition Cross-section of the positive electrode Lithium secondary batteries Viscosity (cps) Agglomeration morphology of conductive materials Battery resistance (mΩ) Example 1 11,900 spherical 1.5 Example 2 10,500 spherical 1.5 Example 3 12,400 spherical / linear 1.5 Comparative Example 1 8,900 linear 1.8 Comparative Example 2 23,000 (Not observed) (Unmeasurable)

[0140] Referring to Table 2, it can be confirmed that, based on the same solids content, the cathode slurry composition of Comparative Example 2, in which the weight-average molecular weight of the dispersant exceeds 150,000 g / mol, has a significantly higher viscosity than the cathode slurry composition of Example 1.

[0141] In Comparative Example 2, the high viscosity of the positive electrode slurry composition caused blockage in the delivery pipe connected to the die coater, preventing the slurry composition from being discharged from the die coater under normal pump pressure. To discharge the positive electrode slurry composition from the die coater, a high pump pressure was required, resulting in excessive pump pressure. Consequently, since the positive electrode slurry composition could not be coated at the same loading as in Example 1, it was impossible to manufacture the positive electrode, and therefore impossible to measure the battery resistance of the lithium secondary battery.

[0142] Although the cathode slurry composition of Comparative Example 1, in which the weight average molecular weight of the dispersant exceeds 150,000 g / mol, has a low viscosity, it has a lower solids content than the cathode slurry composition of Example 1. Therefore, a longer drying time is required in the manufacture of the cathode, thus increasing the process cost.

[0143] Furthermore, it can be confirmed that the lithium secondary battery of Comparative Example 1 exhibits a higher battery resistance than the lithium secondary battery of Example 1. It is speculated that this result is due to the fact that, in the case of Comparative Example 1, such as... Figure 2 As shown, conductive materials agglomerate in a linear form in the positive electrode to increase the surface area of ​​the agglomerated conductive materials, thus increasing the surface area of ​​the positive electrode active material located adjacent to the agglomerated conductive materials and thereby not participating in the lithium insertion / extraction reaction.

Claims

1. A positive electrode slurry composition, said positive electrode slurry composition comprising: a positive electrode active material, a dispersant, a conductive material, a binder, and a solvent. in, The positive electrode active material contains lithium iron phosphate, and The weight-average molecular weight of the dispersant is from 10,000 g / mol to 150,000 g / mol. The dispersant is hydrogenated nitrile butadiene rubber.

2. The positive electrode slurry composition according to claim 1, wherein, The lithium iron phosphate is a compound represented by the following chemical formula 1. [Chemical Formula 1] Li 1+a Fe 1-x M x (PO 4-b )X b In chemical formula 1, M is any one or more elements selected from Al, Mg, Ni, Co, Mn, Ti, Ga, Cu, V, Nb, Zr, Ce, In, Zn, and Y. X is any one or more elements selected from F, S, and N, and a, b, and x satisfy -0.5≤a≤0.5, 0≤b≤0.1, and 0≤x≤0.5, respectively.

3. The positive electrode slurry composition according to claim 1, wherein, The content of the dispersant is from 0.2 parts by weight to 1.0 parts by weight relative to 100 parts by weight of solids in the positive electrode slurry composition.

4. The positive electrode slurry composition according to claim 1, wherein, The solids content in the positive electrode slurry composition is from 40% to 75% by weight.

5. The positive electrode slurry composition according to claim 1, wherein, The positive electrode slurry composition was subjected to 25°C and 10... -2 Viscosities measured at rpm ranged from 5,000 cps to 20,000 cps.

6. The positive electrode slurry composition according to claim 1, wherein, The content of the conductive material is from 0.1 parts by weight to 3.0 parts by weight relative to 100 parts by weight of solids in the positive electrode slurry composition.

7. The positive electrode slurry composition according to claim 1, wherein, The content of the binder is 2.0 to 4.0 parts by weight relative to 100 parts by weight of solids in the positive electrode slurry composition.

8. A lithium secondary battery, said lithium secondary battery comprising a positive electrode, in, The positive electrode comprises a positive electrode active material, a dispersant, a conductive material, and a binder. The positive electrode active material comprises lithium iron phosphate, and In the cross-section of the positive electrode, the maximum major axis length of the agglomerated region of the conductive material is less than 10 μm. The dispersant has a weight-average molecular weight of 10,000 g / mol to 150,000 g / mol. The dispersant is hydrogenated nitrile butadiene rubber.

9. The lithium secondary battery according to claim 8, wherein, The SOC50 discharge resistance of the lithium secondary battery is below 1.7 mΩ.

Citation Information

Patent Citations

  • Positive electrode active material pre-dispersion composition, positive electrode for secondary battery, and lithium secondary battery comprising same

    CN109845005A

  • Aqueous processing of composite lithium ion electrode material

    US20130108776A1